Women's Rebellion in Tarian Bumi: Challenging Patriarchal Culture in Oka Rusmini’s Novel - Weldemina Yudit Tiwery; Jefriyanto Saud; Everhad Markiano Solissa; Cicilia Tantri Suryawati; Rahmi Setiawati (RETORIKA: Jurnal Ilmu Bahasa, 2024)
"In 'Tarian Bumi,' the narrative vividly portrays Balinese women's defiance against the entrenched patriarchal norms of their society. The protagonist, Ida Ayu Telaga, emerges as a symbol of courage, challenging the oppressive customs that confine women's autonomy and expression. This research endeavors to delve into the diverse manifestations of Balinese women's resistance against patriarchal hegemony, employing a feminist lens. Utilizing a descriptive qualitative approach, the study mines the rich textual landscape of 'Tarian Bumi' for instances of women's defiance. The methodology involves a meticulous examination of the novel, supplemented by insights from various secondary sources such as books, theses, articles, and news reports on women's struggles against patriarchy. Through a process of data reduction, classification, and validation, the researcher identifies recurring themes of resistance encoded within the text. The findings underscore a spectrum of challenges, encompassing traditional gender roles, marital expectations, familial constraints, religious and social inequalities, and instances of gender-based violence. These acts of resistance are articulated through diverse mediums including written expressions, philosophical reflections, and symbolic dances—a testament to the enduring struggle for justice. By illuminating these narratives of defiance, the research serves as a catalyst for critical reflection, urging readers to interrogate prevailing patriarchal paradigms and advocate for gender equity."